2014
DOI: 10.1179/1743284713y.0000000422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold rolling on tensile properties and microstructure of high nitrogen alloyed austenitic steel

Abstract: The cold rolling strain effect on the tensile properties of a high nitrogen alloyed austenitic steel was systemically investigated. Quasi-static tensile experiments were performed on the samples with different cold rolling strain. The material possessed good balance between strength and ductility in the entire rolling strain range. Mechanical property and microstructure of the nitrogen alloyed austenitic steel were greatly affected by cold rolling strain. With the increase in cold rolling strain, the strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In CR50_TA sample, the volume of γ-austenite is increased as during thermal ageing, α' and ε- martensite transform into γ-austenite. It is called the reversion of the martensite into the austenitic phase (De et al , 2004; Bansod et al , 2016; Sun et al , 2013). From the above findings, it can be inferred that at a low strain rate, carbide precipitation occurs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In CR50_TA sample, the volume of γ-austenite is increased as during thermal ageing, α' and ε- martensite transform into γ-austenite. It is called the reversion of the martensite into the austenitic phase (De et al , 2004; Bansod et al , 2016; Sun et al , 2013). From the above findings, it can be inferred that at a low strain rate, carbide precipitation occurs.…”
Section: Resultsmentioning
confidence: 99%
“…The author also concluded that there is unavailability of data of cold worked ASS in the standard steel book as the industries have not incorporated cold worked ASS in their applications. Sun et al (2013) investigated the effects of the cold rolling strain on high nitrogen austenitic stainless steels (HNSSs) with two high mill roll that gave 0.2 mm thickness reduction per pass. The authors concluded that HNSS exhibits a satisfactory level of ductility (12.3%-86.6%) and high strength (1001-2236 MPa) as compared to the classical stainless steels.…”
Section: Introductionmentioning
confidence: 99%
“…This result is different from HIP samples at the same solution temperature. In addition, annealing twins (pointed by white arrow in Figure 5(a)) appear in γ grains, and their number increases with increasing solution temperature [28,29]. Similarly, the σ phase can be eliminated when the solution temperature is above 1050°C.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] and thus are becoming an important class of engineering materials. The appropriate analysis of plastic flow behavior or stress-strain curve of HNSs is of critical importance for optimizing their microstructure and mechanical properties and extending their engineering applications.…”
Section: Introductionmentioning
confidence: 99%